Globalization and Digitalization in Education; A Review of Islamic and Western Educational Philosophy - Ulfah, Atiyah; Muhammad Iqbal Noor; Noor, Irfan (Interdisciplinary Explorations in Research Journal, 2023)
ABSTRACT Globalization and digitalization are two phenomena that cannot be separated from human life today, including in the field of education. Globalization has opened wider access to information and communication, while digitalization has presented various technologies that can be used in the learning process.In this paper, we will discuss the impact of globalization and digitalization on education, both from a positive and negative perspective. Positive impacts include increased access and quality of education, while negative impacts include misuse of technology and moral degradation.Islamic education is also not immune from the influence of globalization and digitalization. To face these challenges, Islamic education needs to make various adaptations and innovations, including by developing a curriculum that is relevant to the needs of the times, utilizing technology wisely, and instilling strong moral values. ABSTRAK Globalisasi dan digitalisasi adalah dua fenomena yang tidak bisa dipisahkan dari kehidupan manusia saat ini, termasuk di bidang pendidikan. Globalisasi telah membuka akses yang lebih luas ke informasi dan komunikasi, sementara digitalisasi telah memperkenalkan berbagai teknologi yang dapat digunakan dalam proses pembelajaran. Dalam makalah ini, kita akan membahas dampak globalisasi dan digitalisasi pada pendidikan, baik dari sudut pandang positif maupun negatif. Dampak positifnya meliputi peningkatan akses dan kualitas pendidikan, sementara dampak negatifnya mencakup penyalahgunaan teknologi dan degradasi moral.Pendidikan Islam juga tidak luput dari pengaruh globalisasi dan digitalisasi. Untuk menghadapi tantangan ini, pendidikan Islam perlu melakukan berbagai penyesuaian dan inovasi, termasuk dengan mengembangkan kurikulum yang relevan dengan kebutuhan zaman, menggunakan teknologi dengan bijaksana, dan menanamkan nilai-nilai moral yang kuat.